Abu Bakr Ibn Mujahid dan Qirâ’ah Sab’ah - Nurhidayah, Lilik; Majid, Andi Muhammad Sultan Maulana (Sekolah Tinggi Ilmu Ushuluddin Wadi Mubarak Bogor, 2021)
The problem in this research is the misunderstanding of some of the general public about the meaning of the hadith (seven) of the prophet sallallaahu 'alaihi wasallam. The purpose of this study is to analyze the reasons that prompted Ibn Mujahid to collect seven qirâ`ât in his book